An empirical, pragmatic approach applying reflection in interaction approach to manual therapy treatments. (3rd July 2021) - Tuttle, Neil; Hazle, Charles
ABSTRACT: Background: Most literature on decision processes within physiotherapy relates to "reasoning that results in action" – decisions based on information including assessments that are gathered prior to treatment decisions. A process of "reasoning in interaction" that is often used, particularly by expert clinicians, has received less attention. Objective:   To provide a theoretical and practical approach to applying reasoning in interaction in a musculoskeletal setting. Methods: The theory is: If an impairment that can be directly targeted by treatment (i.e. pain or limitation of passive movement) is related to patient's active impairments and functional limitations, then moment-to-moment changes in the targeted impairment can be used as feedback to guide real-time treatment modification before formal reassessment of functional limitations and other impairments. Results: Applying the theory to manual therapy results in parameters of techniques such as force, speed, direction and duration no longer being pre-determined, but rather being continually adjusted in real-time according to feedback from the patient through both therapist perception (changes in movement quantity or quality) and patient verbal responses. Conclusion: A process of continuous decision-making is described that the authors believe is used by many experienced clinicians but has not previously been adequately described in the literature. .